A dream of justice: the story of Keyes v. Denver Public Schools - Pascoe, Pat, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2022)
A Dream of justice is a firsthand account of the fight to desegregate Denver's public schools. Drawing on oral histories and interviews with members of the school board, legal community, parents, and students, as well as extensive institutional records, Pascoe offers a social history of Keyes v. Denver Public Schools.--Provided by publisher.
Keywords: Segregation in education -- Law and legislation -- Colorado -- Denver; School integration -- Law and legislation -- Colorado -- Denver; Educational law and legislation -- Colorado -- Denver; Keyes, Wilfred, 1925-1999 -- Trials, litigation, etc.; School board members -- Colorado -- Denver -- Biography; Noel, Rachel, 1918-2008; Civil rights workers -- Colorado -- Denver -- Biography; Denver Public Schools -- Trials, litigation, etc.